Populist discourse on a British social media patient-support community: The case of the Charlie Gard support campaign on Facebook. (August 2018) - Das, Ranjana
Abstract: This article analyses discourse on a new and ongoing online patient-support community to demonstrate how it performed populism. It demonstrates how the more than sixty thousand strong social media 'Army' formed around a terminally ill baby at the centre of a parent-judiciary-hospital legal battle, used key tropes and devices of populist rhetoric to establish lay-expertise in its performance of support for the ordinary patient and their family, de-recognizing and vilifying medical expertise and publicly funded healthcare systems built on socio-democratic ideals. The article shows how users' mobilization of populist rhetoric to reject professional expertise and public institutions, made use of established architectural features of the online community's socio-technological design, such as immediacy, remediation and protective gatekeeping. The paper argues that this fed into and out of an environment of disdain for public services and expertise in contemporary UK.